Deliberative democracy and divided societies - O'Flynn, Ian. (Edinburgh : Edinburgh University Press, 2006)
In a world where the impact of internal conflicts is spreading ever wider, there is a real need to rethink how democratic ideals and institutions can best be implemented. This book responds to this challenge by showing that deliberative democracy has crucial, but largely untapped, normative implications for societies deeply divided along ethnic lines. Its central claim is that deliberative norms and procedures can enable the citizens of such societies to build and sustain a stronger sense of common national identity. More specifically, it argues that the deliberative requirements of reciprocity and publicity can enable citizens and representatives to strike an appropriate balance between the need to recognise competing ethnic identities and the need to develop a common civic identity centred on the institutions of the state. Although the book is primarily normative, it supports its claims with a broad range of empirical examples, drawn from cases such as Bosnia and Herzegovina, Lebanon, Macedonia, Northern Ireland and South Africa. It also considers the normative implications of deliberative democracy for questions of institutional design. It argues that power-sharing institutions should be conceived in a way that allows citizens as much freedom as possible to shape their own relation to the polity. Crucially, this freedom can enable them to reconstruct their relationship to each other and to the state in ways that ultimately strengthen and sustain the transition from ethnic conflict to democracy.
Cover -- Contents -- Acknowledgements -- Introduction -- Introduction -- Why deliberative democracy63; -- What this book will argue -- Chapter 158; Locating the Discussion -- The consociational model -- The normative8211;empirical interface -- Two problems with normative standards -- Treading the middle ground -- Chapter 258; Division44; Democracy and Deliberation -- The basic problem -- Ethno45;national conflict -- Democratic values -- Intrinsic equality -- Intrinsic equality -- Personal autonomy -- Defining deliberative democracy -- Chapter 358; Deliberating National Identity and Citizenship -- Civic and ethnic nationalism -- Liberalism -- Republicanism -- The deliberative alternative -- Chapter 458; The Requirement of Reciprocity -- What is reciprocity63; -- Reciprocity versus combat -- Reciprocity and bargaining -- Reciprocity and voting -- Reciprocity and the creation of shareable goods -- The content of public reason -- Chapter 558; The Requirement of Publicity -- Justifying publicity -- The difficulties of negotiating peace agreements -- Levelling the playing field -- Making secrecy public -- Chapter 658; Dilemmas of Exclusion -- Political exclusion -- Is deliberative democracy exclusionary63; -- Expanding the content of democratic deliberation -- From particular stories to general principles -- Chapter 758; Civil Society and Political Institutions -- Civil society -- Consociational democracy revisited -- Segmental autonomy -- Electoral systems -- Legislatures and governing coalitions -- Concluding remarks -- Bibliography -- Index -- Last Page.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Democracy; Nationalism; Ethnic relations -- Political aspects; Ethnic conflict -- Prevention; Nationalisme; Relations interethniques -- Aspect politique; nationalism; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Democracy; Ethnic conflict -- Prevention; Ethnic relations -- Political aspects; Nationalism; Deliberative Demokratie; Gesellschaft; Democratie; Nationalisme; Sociale conflicten; Electronic books; Electronic books